Acute and Long-Term Angiographic Outcomes of Side Branch Stenosis after Randomized Treatment of Zotarolimus-, Sirolimus-, and Paclitaxel-Eluting Stent for Coronary Artery Stenosis - Lee, Bong-Ki (The Korean Academy of Medical Sciences, 2012)
This was designed to assess the outcomes of side branch (SB) stenosis after implantation of three drug-eluting stents (DES). From 2,645 patients in the ZEST (Comparison of the Efficacy and Safety of Zotarolimus-Eluting Stent with Sirolimus-Eluting and PacliTaxel-Eluting Stent for Coronary Lesions) Trial, 788 patients had 923 bifurcation lesions with SB ≥ 1.5 mm were included. SB was treated in 150 lesions, including 35 (3.8%) receiving SB stenting. Of untreated SB with baseline stenosis < 50%, the incidences of periprocedural SB compromise was similar in the zotarolimus (15.8%), sirolimus (17.2%), and paclitaxel (16.6%) stent groups (P = 0.92). At follow-up angiography, delayed SB compromise occurred in 13.9%, 3.2%, and 9.4% (P = 0.010) of these groups. When classified into four groups (< 50%, 50%-70%, 70%-99%, and 100%), 9.0% of untreated SB were worsened, whereas improvement and stationary were observed in 9.6% and 81.4%. In a multivariable logistic regression model, main branch (MB) stenosis at follow-up (%) was the only independent predictor of SB stenosis worsening (odds ratio, 1.03; 95% confidence interval, 1.01-1.04; P < 0.001). After MB stenting in bifurcation lesions, a minority of SB appears to worsen. DES with strong anti-restenotic efficacy may help maintain SB patency.